Pelatihan Step By Step Pembuatan Blog Menggunakan Wordpress untuk Remaja Desa Tegal Arum - Kadarsih Kadarsih; Defi Pujianto; Mita Agustina; Amanda Rahayu Astuti; Putri Wahyu Kirani; Yohana Fransisca Dessy Kristianti; Heru Jun Samudra (Universitas Pahlawan Tuanku Tambusai, 2023)
Blog making training using Wordpress in Tegal Arum OKU village. The target of this training is youth. The reason for choosing the topic is the gadget that has changed the routine of teenagers which is not always positive. Sometimes the use of gadgets is not optimal. Based on this, training activities for making Blogs are carried out. The goal is to share knowledge to create a digital footprint. Training is given directly and practiced using gadgets. Through this service activity, youth have knowledge of how to create a blog using Wordpress.